Correction to: Inpatient versus outpatient induction of labour: a systematic review and metaanalysis - Susan Dong; Maria Khan; Farahnosh Hashimi; Caroline Chamy; Rohan D'Souza (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.